Interleukin-2 receptor β chain as a possible target for low doses of mafosfamide - A. Pukhalsky; A. Toptygina; S. Khaidukov (Mediators of Inflammation)
The 7-day cytotoxic lymphocytes (CTL) induced in mixed lymphocyte culture express only the chain of the interleukin-2 receptor (IL-2R). In the present study this fact has been confirmed in a murine semi-allogeneic system. The ability of low doses of mafosfamide (Mf) to affect IL-2-induced CTL proliferation has been demonstrated. It was also shown that IL-2 activated resting suppressor cells. The pretreatment of the suppressor cells with either monoclonal antibodies (mAbs) against the p75 chain of IL-2R, or with Mf abolished the suppressive effect of these cells. No restoration of the proliferative response occurred when the anti-IL-2Rα mAb had been used. Flow cytometry analysis of 7-day CTL was carried out with mAbs against the α and β chains of IL-2R. CTL treatment with Mf inhibited anti-IL-2Rβ mAb binding. It may be assumed that the anti-proliferative effects of Mf which have been demonstrated in this paper, were a result of blocking the IL-2R β chain.